Genetic diversity and differentiation of cultured and wild yesso scallop (Mizuhopecten yessoensis) from China revealed by whole genome resequencing - Xinyi He; Shuo Wang; Weiming Teng; Hualin Li; Xi Xie; Shikai Liu; Dacheng Li; Zuoan Yu; Xiangfeng Liu; Zunchun Zhou; Yaqing Chang; Haijiao Liu; et al. (Aquaculture Reports)
One of the main bivalve species used in aquaculture in China is the yesso scallop (Mizuhopecten yessoensis). Nevertheless, little is known about the genetic diversity and stock structure of M. yessoensis during long-term culture processes. This study aims to investigate the genetic diversity and differentiation of cultured stocks in relation to the wild counterparts in the cultivation area and assess the genetic status during long-term aquaculture of M. yessoensis in Dalian. In this study, the whole genome resequencing was used to characterize the genetic diversity of six M. yessoensis stocks in Dalian over the past decade. A total of 15,064,530 SNPs with high quality was detected. The results revealed that the low genetic diversity and heterozygosity, as well as weak genetic differentiation (Fst < 0.05) occurred between paired stocks. AMOVA indicated that most of the genetic variation was found within stocks, and there was no significant differentiation between the cultured and wild groups, or among the stocks within each group, possibly due to frequent gene flow. The small effective population size (Ne) suggested that M. yessoensis might have been affected by limited brood stocks, resulting in genetic drift and exhibiting signs of inbreeding depression. These findings provided valuable insights into the current genomic resources for M. yessoensis and held practical implications for scallop aquaculture.